Natural and Anthropogenic Influences on the Adaptive Potential of Large Mammal Isolated Populations. - FABBRI, Giulia (Università degli studi di Sassari, 2023)
Large mammals are charismatic species that have always interacted with humans. Many of these interactions deserve active management that should consider ongoing evolutionary processes including man-mediated selection and local adaptation. The wild boar (Sus scrofa) and the wolf (Canis lupus) are two widespread, emblematic species of managerial interest. Sardinian and peninsular Italian wild boars were differentiated from other European populations. The heterogeneity of past population histories and management approaches was mirrored by a variegated situation across the Italian peninsula. Signs of translocations from other European countries were negligible, while internal translocations possibly involving one of the best-preserved Italian populations as source were found. The evolution of the wild boar in Corsica and Sardinia, which led to the subspecies S. s. meridionalis, appeared to be the result of adaptations developed on the islands, with signs of selection at elements possibly implied in the regulation of gene expression. Focusing on the Sardinian wild boar, the genetic differentiation can be partially attributed to differences in temperature and precipitation regime across the island. Moreover, domestic introgression was not detected in several samples, but evidence of adaptive introgression at genomic regions of swine origin with a role in reproductive success emerged. The positive influence on the fitness of wild populations due to introgression from the domestic counterpart was demonstrated in the Italian wolf too: the spread of a dog-derived allele at a β-defensine gene appeared to be governed by trade-offs between survival and reproductive success. This thesis demonstrates, with a population genomics approach, that even long-lived species like the two large mammals considered can adapt to the local environmental conditions in short evolutionary time-frames and that different kinds of anthropic interference could have modified their evolutionary trajectories Large mammals are charismatic species ...